The Historic Sebou Basin: An asset of universal value - Ajaraam, Reda; Chergui, Abdelkader; El Bouzidi, Said (Ex Novo: Journal of Archaeology, 2025)
The Sebou Basin, located in northern Morocco, stands as a cultural and natural heritage of universal significance, demonstrating the interplay between various civilisations and a rich environment. This region is home to prominent sites such as Banasa, Thamusida, Rirha, and Mehdia, reflecting periods from prehistory to the Islamic and modern eras. Archaeological discoveries highlight cultural exchanges among Phoenicians, Romans, Mauretanians, and Islamic dynasties. The Sebou River, a central pillar of the region, has been pivotal in fostering the growth of early settlements, trade hubs, and agricultural infrastructure since antiquity. This area also exemplifies harmony between natural heritage and human activity, housing protected areas like the Sidi Boughaba Reserve, renowned for its unique biodiversity and its role in environmental education. UNESCO recognition would enhance the preservation of these treasures and promote sustainable development while celebrating a rich history where nature and culture interweave.